Evaluation of Law Number 6 of 2014 concerning Villages at the Office of the Bubusan Village Head, Jejawi District, Ogan Komering Ilir Regency : (Case Study Article 94 Paragraph 3) - Mayamin Mayamin (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the supervision of the government and the Village Consultative Body (BPD) on the management of the implementation of village development and community empowerment and what factors influence the implementation of village development and community empowerment in Bubusan Village, Jejawi District. The method used in this research is qualitative method. The main data collection techniques are: Observation, interview, and documentation. The results of this study indicate that the Village Government and BPD with fairly good supervision, and wise enough because every activity of the Village government carrying out development is given constructive criticism and suggestions from the BPD, but there are still many shortcomings, especially inadequate facilities and infrastructure, including the absence of BPD office. The community empowerment program in Bubusan Village, Jejawi District is going well, it is proven that the government and BPD have created several organizations, including farmer organizations, fishermen, and the Youth Mosque Association (IRMA), Youth Organizations and others. The factors that influence the implementation of village development and community empowerment in Bubusan Village, include: Human Resources (HR) are not supportive, the community is not aware of the village environment. Like the maintenance of MCK, the community is less attentive, and the community is less concerned about training, both courses and other coaching.